A case of partial trisomy 17 resulting from X-autosomal translocation. Issue 5 (October 1979) - Yamamoto, Y; Endo, Y; Kuroki, Y
Abstract : A case of partial trisomy 17 with partial monosomy X resulting from a maternal X-autosomal translocation t(X;17)(q13;q21) is presented. Three previously reported cases are reviewed and the phenotypic features of trisomy 17 are discussed.